The wind rises [videorecording (DVD)] - Krasinski, John, 1979-; Gordon-Levitt, Joseph, 1981-; Blunt, Emily (Walt Disney Studios Home Entertainment, 2014)
Jiro dreams of flying and designing beautiful airplanes, inspired by the famous Italian aeronautical designer Caproni. Nearsighted from a young age and unable to be a pilot, Jiro joins a major Japanese engineering company in 1927 and becomes one of the worlds most innovative and accomplished airplane designers. Jiro meets and falls in love with Nahoko, and grows and cherishes his friendship with his colleague Honjo. The film chronicles much of his life, depicting key historical events.